MESENTERIAL THROMBOSIS COMPLICATION AND PREVENTION MEASURES AFTER BARIATRIC SURGERY IN PATIENTS WITH MORBID OBESITY - Oktyabr R. Teshaev; Alijon S. Murodov (Central Asian Journal of Medicine, 2024)
mesenteric thrombosis (MVT) after bariatric procedures in patients with morbid obesity. Our research work was carried out on the basis of bariatric surgery performed on 3100 patients in the clinical bases of the TMA Department of Surgical Diseases in Family Medicine. For our research work, the age range was 18 to 63 years. 2542 (82%) of the patients who applied were women, 868 (28%) were men. 2201(71%) patients underwent LOBR, 837(27%) gastric bypass procedures and 62(2%) patients underwent bipartite sleeve bypass surgery. Mesenteric venous thrombosis was detected in 4 (0.1%) patients after the operation. 3(75%) of these patients underwent LOBR and 1(25%) underwent MGB. The main clinical symptoms observed in patients were as follows: abdominal pain (91.8%), daytime nausea and vomiting (30.8%), fever and bloody diarrhea - 10% of cases. Abdominal restlessness, constipation and bowel obstruction, tachycardia, SSVR symptoms were also observed. Complications of MVT in patients were observed on average 16±3 days after surgery. In these patients, relaparoscopy and relaparotomy were performed, resection of the necrotic small intestine was performed, eunodesens in 3 cases and jejunotransverse anastomosis was placed in one case. Proper selection of patients before bariatric surgery, elimination of risk factors leading to MVT, complete thromboprophylaxis before and after surgery, prevention of severe dehydration of patients after the operation can significantly reduce the complication of MVT.